If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + 3y + -3 = 6y + 7 + -2y Reorder the terms: 4 + -3 + 3y = 6y + 7 + -2y Combine like terms: 4 + -3 = 1 1 + 3y = 6y + 7 + -2y Reorder the terms: 1 + 3y = 7 + 6y + -2y Combine like terms: 6y + -2y = 4y 1 + 3y = 7 + 4y Solving 1 + 3y = 7 + 4y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-4y' to each side of the equation. 1 + 3y + -4y = 7 + 4y + -4y Combine like terms: 3y + -4y = -1y 1 + -1y = 7 + 4y + -4y Combine like terms: 4y + -4y = 0 1 + -1y = 7 + 0 1 + -1y = 7 Add '-1' to each side of the equation. 1 + -1 + -1y = 7 + -1 Combine like terms: 1 + -1 = 0 0 + -1y = 7 + -1 -1y = 7 + -1 Combine like terms: 7 + -1 = 6 -1y = 6 Divide each side by '-1'. y = -6 Simplifying y = -6
| a-3.54=8.70 | | 8x+8.52=2x+18 | | -6y=2.46 | | x+2.4=7.3 | | -12=5m^2+16m | | 0.5x+0.3=0.8x-0.3 | | 3m^2+32m=-20 | | 3(h-5)=-4h+19 | | 44x-13=6(7x-3)+2x+5 | | -20=3m^2+32m | | (x^3-6x^2+3x+8)-(3x^2-4x+3)= | | -19-34=56-1x | | 5y+3(y-9)=5(y+1)-4 | | 7x-8=-116-2x | | 9+=5x-3 | | 4t-3=5t+6 | | logx(1000)=3 | | -2x-5=7x+55 | | 12x-28=-63+2x | | 4x-8=8+2x | | 3x+6=-14+7x | | -6-2x=6x+2 | | 6(5x+3)=30x+18 | | r^2/10r-24 | | 25n-15n^2= | | 2(23)-3(5)+32= | | x-8+16=34 | | x-4+8=34 | | -9=5v+6 | | -5a+16+9a=4a-8a | | -5=4/w+5 | | 5m+24+3m=32 |